Subcutaneous fat necrosis of the newborn. Issue 12 (5th November 2015) - Rubin, Giulia; Spagnut, Giulia; Morandi, Francesco; Valerio, Enrico; Cutrone, Mario
Key Clinical Message: Subcutaneous fat necrosis (SCFN) is a rare fat tissue inflammation of the newborn. Risk factors include cord prolapse, perinatal asphyxia, therapeutic hypothermia, meconium aspiration, and sepsis. When present, hypercalcemia comes with lethargy, hypotonia, irritability, vomiting, polyuria, polydipsia, constipation, and dehydration. Kidney injury must be avoided. SCFN is often completely autoresolutive. Abstract : Subcutaneous fat necrosis (SCFN) is a rare fat tissue inflammation of the newborn. Risk factors include cord prolapse, perinatal asphyxia, therapeutic hypothermia, meconium aspiration, and sepsis. When present, hypercalcemia comes with lethargy, hypotonia, irritability, vomiting, polyuria, polydipsia, constipation, and dehydration. Kidney injury must be avoided. SCFN is often completely autoresolutive.